PENGARUH TINGKAT SUKU BUNGA DEPOSITO DAN JUMLAH NASABAH TERHADAP JUMLAH DANA DEPOSITO BERJANGKA PADA PT BANK NEGARA INDONESIA (PERSERO) TBK CABANG LHOKSEUMAWE - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2019)
The purpose of this study is to determine the effect of deposit rates and the number of customers on the amount of deposit funds in PT BNI Lhokseumawe Branch. The object of research in this research is PT BNI Cabanag Lhokseumawe period 2014-2016. From result of research indicate that deposit interest rate and number of customer together have significant effect to amount of deposit fund at PT BNI Lhokseumawe Branch. Partially, the deposit rate has positive and significant effect on the amount of deposit funds in PT BNI Lhokseumawe Branch, and the customers has a positive and significant effect on the amount of deposit funds in PT BNI Lhokseumawe Branch